2020
DOI: 10.1002/cam4.3116
|View full text |Cite
|
Sign up to set email alerts
|

Second‐line treatment of hepatocellular carcinoma after sorafenib: Characterizing treatments used over the past 10 years and real‐world eligibility for cabozantinib, regorafenib, and ramucirumab

Abstract: BackgroundThe CELESTIAL, RESORCE, and REACH‐2 trials showed survival benefit of cabozantinib, regorafenib, and ramucirumab, respectively, in hepatocellular carcinoma (HCC) patients treated with sorafenib who had good performance status (ECOG 0‐1) and liver function (Child‐Pugh‐A). This study characterizes subsequent treatments received by HCC patients after sorafenib, and determines the proportion of patients eligible for novel therapies if strict eligibility criteria (SEC) were utilized compared to more liber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…For instance, Fung et al [24] reported that only 13.1% of 720 sorafenib-experienced patients were eligible for cabozantinib, regorafenib, or ramucirumab as a second-line treatment if strict eligibility criteria were used. If the eligibility criteria were extended to also include patients with ECOG-PS 2 or Child-Pugh class B7, then the eligibility rate increased to 31%, but with a lesser survival expectancy [24]. The proportion of patients theoretically eligible for a third-line treatment has never explicitly been investigated, but the proportion is expected to be even lower than that reported for the second-line setting.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Fung et al [24] reported that only 13.1% of 720 sorafenib-experienced patients were eligible for cabozantinib, regorafenib, or ramucirumab as a second-line treatment if strict eligibility criteria were used. If the eligibility criteria were extended to also include patients with ECOG-PS 2 or Child-Pugh class B7, then the eligibility rate increased to 31%, but with a lesser survival expectancy [24]. The proportion of patients theoretically eligible for a third-line treatment has never explicitly been investigated, but the proportion is expected to be even lower than that reported for the second-line setting.…”
Section: Discussionmentioning
confidence: 99%
“…It also determined the rate of patients eligible for new therapies if strict eligibility criteria (SEC; as defined in the respective studies) were used, compared with more liberal modified eligibility criteria (MEC, including Child–Pugh-B7 and ECOG 2). 61 …”
Section: Regorafenib Treatment In Real-life Clinical Practicementioning
confidence: 99%
“…A Canadian study characterized subsequent therapies received by HCC patients following sorafenib and determined the rate of patients eligible for novel therapies if strict eligibility criteria (SEC) (as defined in their respective trials) were used, compared to more liberal modified eligibility criteria (MEC, including Child-Pugh B7 and ECOG 2). 58 A total of 730 patients were identified with 172 (23.6%) receiving subsequent treatment (regorafenib, cabozantinib or ramucirumab). Patients receiving subsequent treatment had longer overall survival than patients who did not (12.1 versus 3.3 months; p<0.001).…”
Section: Dovepressmentioning
confidence: 99%
“…A Canadian study characterized subsequent therapies received by HCC patients following sorafenib and determined the rate of patients eligible for novel therapies if strict eligibility criteria (SEC) (as defined in their respective trials) were used, compared to more liberal modified eligibility criteria (MEC, including Child–Pugh B7 and ECOG 2). 58 …”
Section: Real-life Clinical Practice Of Regorafenib Treatment In Hccmentioning
confidence: 99%